Santri Digital Literacy Training for Entrepreneurship: at Pondok Pesantren At-Tamimy Berangsak in Central Lombok - Rumba, Rumba (Masyarakat Pariwisata : Journal of Community Services in Tourism, 2024)
The santri digital literacy training for entrepreneurship is designed to enhance the digital skills of entrepreneurs in navigating the challenges of the digital era. Scheduled on June 26, 2024, at Pondok Pesantren At-Tamimy Berangsak in Central Lombok, this training aims to improve participants' understanding and application of digital technologies for managing and growing their businesses. The program will cover digital marketing strategies, data analysis, social media management, and e-commerce platforms. Keynote speakers include a representative from the Executive Board of Better Together Indonesia Foundation Jakarta and a lecturer from the Entrepreneurship Unit of Politeknik Pariwisata Lombok, who will provide insights on digital strategies and practical case studies. This hands-on training is intended to empower entrepreneurs with relevant skills and effective strategies to enhance their competitiveness in the ever-evolving digital market.